Sistem Monitoring Online Real Time Beban Unbalance dan Overload Trafo Distribusi di PT PLN (Persero) - Musthofa Musthofa (Sekolah Tinggi Teknik PLN, 2020)
Public and government demands for PLN to serve all people to enjoy electricity with a target of 100% Electrification Ratio. To fulfill the Electrification Ratio, of course, it is necessary to increase the capacity of the distribution transformer with the addition of an insert transformer and a new transformer. So that the increasing number of connections to customers' homes or buildings will result in overload or unbalance loading of the distribution transformer. The problem is the number of transformers 3,938 units at PLN UP3 Padang with limited load measuring officers only 70 teams, there is still a transformer failure of 0.41% in 2019. This is because the load measurement is done directly (manually on site) so it requires large human resources and costs. Under these conditions, a realtime online load measurement system is needed. This study uses the Root Couse Problem Solving (RCPS) methodology and system and equipment design by creating a transformer load monitoring system both unbalance and overload online Real Time. With this System and Equipment, the substation load in realtime with a speed of 2 seconds, the condition of the transformer is known. Telemetering function by sending load data so that the risk of damage to the transformer can be reduced because this tool is an early warning against unbalanced loads, single phase outages and so on. So that PLN can maintain life time and recovery time in maintaining the quality of its service.